Difference-based analysis of the impact of observed game parameters on the final score at the FIBA Eurobasket Women 2019 - Simovic, S.; Komic, J.; Guzina, B.; Pajic, Z.; Karalic, T.; Pašic, G. (Journal of Human Sport & Exercise, 2021)
Evaluation in women's basketball is keeping up with developments in evaluation in men`s basketball, and although the number of studies in women's basketball has seen a positive trend in the past decade, it is still at a low level. This paper observed 38 games and sixteen variables of standard efficiency during the FIBA EuroBasket Women 2019. Two regression models were obtained, a set of relative percentage and relative rating variables, which are used in the NBA league, where the dependent variable was the number of points scored. The obtained results show that in the first model, the difference between winning and losing teams was made by three variables: true shooting percentage, turnover percentage of inefficiency and efficiency percentage of defensive rebounds, which explain 97.3%, while for the second model, the distinguishing variables was offensive efficiency, explaining for 96.1% of the observed phenomenon. There is a continuity of the obtained results with the previous championship, played in 2017. Of all the technical elements of basketball, it is still the shots made, assists and defensive rebounds that have the most significant impact on the final score in European women`s basketball. It can be noted that, unlike with the previous championship, inside play is no longer dominant, but there is a balance between inside and outside play, which has already been established as a developing trend in men`s basketball. The emergence of the offensive efficiency variable indicates that it is becoming significant in top-tier competitions as well but is still a challenge for coaches to grasp the causes of this multicomplex issue based on this indicator.